Analisis Sentimen Twitter Ibu Kota Negara Nusantara Menggunakan Algoritma Naive Bayes, Logistic Regression dan K-Nearest Neighbors - Sativa, Alisya Nisrina; Rizky, Avinka; Imelda Putri; Putri, Juventia Adelia; Akhmad Irsyad; Islamiyah (Adopsi Teknologi dan Sistem Informasi (ATASI), 2024)
Indonesia plans to move its capital from Jakarta to eastern Kalimantan under the name Nusantara. On the other hand, the new capital-building plan of Nusantara in eastern Kalimantan is called a public policy expert that will squeeze the state's incomes and expenditure (APBN) budget post in the midst of massive spending on health care and economic recovery from the Covid-19 pandemic. The relocation plan harvested a number of citizens' opinions on Twitter. The sentiment analysis research was conducted to find out the response of tweets related to the transfer of the Indonesian capital after the passing of the ICT Act as well as the comparison of the number of positive and negative tweets. The analysis process involves processing text data, creating a word cloud, and applying regression algorithms like Logistic Regression, classifications like Naive Bayes and K-Nearest Neighbors to predict sentiment. The Naive Bayes model's accuracy is the best algorithm model achieving a precision of 0.9480, with precision 0.9399, recall 0.9609, and f1-score 0.9503. This research provides in-depth insight into public opinion related to the transfer of the state capital of Nusantara.